Exploring teachers' perceived intrinsic cognitive load while learning to use visual thinking tools - Zhao, Guoqing; Sheng, Haixi; Yan, Xiaomei; Xiong, Yawen; Zhou, Xinran (American Journal of Education and Learning, 2024)
This study aims to explore the potential extraneous cognitive load (ECL) that learners may encounter when using visual thinking tools (VTTs) as pedagogical aids, which is comparable to the intrinsic cognitive load (ICL) associated with these tools' learning process. An online questionnaire adapted from the Cognitive Load Scale was sent to in-service teachers who participated in a 21-day online training course on three VTTs (thinking maps, mind maps, and concept maps), and 220 valid responses were collected. We conducted a two-way ANOVA with repeated measures to analyze the differences in the teachers' perceived ICL at different learning levels for each VTT. The participants’ homework and feedback are also collected and analyzed to triangulate the results from the questionnaire. A two-way ANOVA with repeated measures was conducted to analyze the differences in the teachers' perceived ICL at different learning levels for each VTT. The participants’ homework and feedback are also collected and analyzed to triangulate the results from the questionnaire. The results reveal that: 1) Concept maps, thinking maps, and mind maps have the highest perceived ICL, ranging from high to low. 2) Among the four learning levels (understanding, manipulating, applying, and evaluating), the participants perceive the slightest ICL at the applying level for all three VTTs. 3) Thinking maps, mind maps, and concept maps cause the heaviest ICL at the understanding, evaluating, and manipulating levels, respectively. Implications for designing professional development programs on VTTs were discussed.